EFEKTIVITAS BETAIN PADA PAKAN AYAM BROILER RENDAH METIONIN BERDASARKAN PARAMETER BERAT BADAN DAN KARKAS - Adi Ratriyanto; Rysca Indreswari; Sudiyono Sudiyono (Caraka Tani: Journal of Sustainable Agriculture, 2012)
This experiment was conducted to investigate the efficacy of methyl groups donor of betaine to spare methionine based on performance and carcass in broiler chickens. In total, 100 day old broiler chickenss were used in this experiment. They were allocated to 4 dieaty treatmants in 5 replicates with 5 broilers each. The basal diet was deficient in methionine. The control diet was obtained from basal diet supplemented with methionine to meet the requirements 5 g/kg diet for starter period and 3.8 g/kg diet for finisher period. The rest 3 treatments were basal diet deficient in methionine supplemented with 1, 2 and 3 g betaine per kg diet. The variables that were observed included average daily gain and carcass characteristics. The data were than analyzed by analysis of variance of Completely Randomized Design and continued with Dunnet test. The result indicated that supplementation of 1 and 2 g betaine per kg diet deficient in methionine resulted the broiler performance which was not different with supplementation of methionine. Accordingly, carcass characteristics for broilers fed diet supplemented with methionine were not different with that supplemented with betaine, which indicated that betaine may reduce the methionine level in the broiler diet. It can be concluded that betaine spares metionine in broiler diets.